2015
DOI: 10.1208/s12248-015-9751-7
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro, Pharmacokinetic, Pharmacodynamic, and Safety Comparisons of Single and Combined Administration of Tiotropium and Salmeterol in COPD Patients Using Different Dry Powder Inhalers

Abstract: Abstract. In vitro Andersen cascade impactor-sized mass (ISM) and aerodynamic fine particle mass (FPM) <5 μm for tiotropium and salmeterol combined in a novel inhalation powder formulation containing 7.5 μg tiotropium/ 25 μg salmeterol (TSHH) were similar (within ±15%) to reference products containing 18 μg of tiotropium (Spiriva® HandiHaler®) (TioHH) and 50 μg of salmeterol (Serevent® Diskus®) (SalD). The pharmacokinetics (PK), pharmacodynamics, safety, and tolerability of the novel fixed-dose TSHH formulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
12
0
3
Order By: Relevance
“…Besides, it has been suggested that for lipophilic substances, such as salmeterol, delayed pulmonary dissolution may lead to a prolonged pulmonary absorption and also contribute to the later absorption phase observed for salmeterol (Horhota et al, ; Weber & Hochhaus, ). Likewise, the presence of flip‐flop kinetics in the later absorption phase and a possible mismatching of the estimated oral absorption rate constant with the disposition parameters cannot be excluded as well.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it has been suggested that for lipophilic substances, such as salmeterol, delayed pulmonary dissolution may lead to a prolonged pulmonary absorption and also contribute to the later absorption phase observed for salmeterol (Horhota et al, ; Weber & Hochhaus, ). Likewise, the presence of flip‐flop kinetics in the later absorption phase and a possible mismatching of the estimated oral absorption rate constant with the disposition parameters cannot be excluded as well.…”
Section: Discussionmentioning
confidence: 99%
“…These present a major challenge in bioanalytical method development and pharmacokinetic parameter estimation for bioavailability and bioequivalence studies . In earlier studies, the bioanalytical methodology that was used for analyzing tiotropium in plasma (liquid chromatography coupled to tandem mass spectrometry [LC‐MS/MS]) had a lower limit of quantitation (LLOQ) of 2.5 pg/mL . Table shows the numbers of subjects with plasma concentrations of tiotropium above the LLOQ (2.5 pg/mL) following a single administration of 18 μg tiotropium to healthy volunteers.…”
Section: Bioanalytical Methods and Implications For Pharmacokinetic Pamentioning
confidence: 99%
“…The reviews of the workshops, although comprehensive, do not address specific bioequivalence requirements for tiotropium bromide (trade name, Spiriva). Specifically for tiotropium, it was recently shown that the in vitro tests conducted for the development of a new OIP containing tiotropium were not predictive of the systemic exposure …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The following review papers in this issue provide an integrated view of talks and discussions related to a given topic: & Application of the modified chi-square ratio statistic in a stepwise procedure for cascade impactor equivalence testing (by Ben Weber et al) (6) & Effect of device design and formulation on the in vitro comparability for multi-unit dose dry powder inhalers (by Jag Shur et al) (7) & In vitro, pharmacokinetic, pharmacodynamic, and safety comparisons of single and combined administration of tiotropium and salmeterol in COPD patients using different dry powder inhalers (by Stephen Horhota et al) (8) & Safety of β2-agonists in asthma: linking mechanisms, meta-analyses, and regulatory practice (by Sanjeeva Dissanayake) (9).…”
Section: Introductionmentioning
confidence: 99%